The Impact of Online Learning on Academic Performance Mediated by Student’s Commitment: A Study on Malaysian Public Universities - Taip, Nurul Affahida; Norazidah, Shamsudin; Suhana, Mohamed; Yau'mee Hayati, Hj Mohamed Yusof (GBMR, 2023)
Purpose: Due to Covid-19, online learning is extensively adopted by the education industry and is a common learning method nowadays. Even though it is preferred by most of the education providers, nevertheless, the student's performance is more pertinent. This research has been conducted to investigate the impact of online learning on the academic performance of public university students in Malaysia mediated by the student's commitment. Therefore, the objective of the study is to 1) examine the effect of online learning on academic performance; 2) investigate the effect of online learning affecting student commitment; 3) analyze the effect of student commitment on academic performance. Design/methodology/approach: This study is a quantitative study which the data gathered through questionnaire. PLS-SEM software version 3.3.3 was used to analyze the data obtained from 119 students at a Malaysian public university. Findings: The result indicates that online learning positively impacts academic performance and student’s commitment, and a positive relationship between student’s commitment and academic performance. Thus, all hypotheses are found to be supported. Research limitations: The study is limited to Malaysian public university only. Basically, the study is limited to three main variables that are independent variable which represent by online learning (learning platform, interaction, and technology); mediating variable which represent by student commitment (learning environment, time allocation, and peer relationship); and dependent variable of academic performance (CGPA and practical skill). Practical implications: It was determined that the findings of the study prove the impact of online learning on academic achievement as mediated by student commitment were important. As a result, online learning has a favourable effect on students' dedication and academic achievement. The findings might be significant to other institutions and at different level of education as well, hence, other variables could be explored. Lecturer, teachers, and education institutions should consider on improving the learning platform, interaction, and technology for the online learning efficiency. Whereas the student themselves should improve their learning environment, time allocation, and peer relationship in ensuring better academic performance particularly on CGPA and practical skill. Originality/value: This study focuses on variables and factors which could improve a student’s academic performance mainly on online learning mode. The data been collected after Covid-19 strikes which the online learning becomes the main platform and the only option that the student could go for. Therefore, the respondent’s feedback in the study might different compared to other research about online learning which the mode is voluntarily chosen by the student.